Iron-core/carbon-shell nanoparticles with intrinsic peroxidase activity: new platform for mimetic glucose detection; Analytical Methods; Vol. 9, iss. 16 - Surgutskaya N. S. Nataliya Sergeevna; Trusova M. E. Marina Evgenievna; Slepchenko G. B. Galina Borisovna; Minin A. S.; Pershina A. G. Aleksandra Gennadievna; Uimin M. A.; Yermakov A. E.; Postnikov P. S. Pavel Sergeevich (2017, 2017)
Title screen